Quality of Life and Quality of Working Life - Alice Vilas Boas, Ana (IntechOpen, 2017)
In this book, we can read about the well-being, quality of life, and quality of working life. The authors come from different countries, and their ideas, studies, findings, and experiences offer beneficial contributions to enhance our knowledge in the field of well-being and quality of life, as well as quality of working life. The book is divided into two sections, and their respective chapters refer to two major areas. The first section covers "Different Perspectives of Quality of Life," considering the antecedents of happiness, quality of life and sports, quality of life indexes for the United States, well-being in the context of family policies in European countries, cultural well-being and income in Italy, and the right to life in South Africa. The second section deals with "Well-Being and Quality of Working Life," emphasizing these topics for university professors in Brazil, as well as work-related well-being, psychological well-being of individuals as employees, physical and psychical well-being and stress, human work in organizations considering the discomfort perspective, and professional pride and dignity among social workers. Thus, we consider this book will be of interest for readers with a diverse group of audience in different areas of specialty such as psychology, industrial and social psychology, management, medicine, education, law, and sociology.